Learning from ancient water management: Archeology's role in modern‐day climate change adaptations. (15th October 2017) - Kaptijn, Eva
Abstract : Climate change is altering our environment and societies worldwide have to devise adaptation strategies. Water management strategies are becoming especially important. In the past, societies had to adapt in order to survive as well. Communities often practised long‐term sustainable agriculture. By understanding the ways in which ancient communities were successful at or failed in attaining social‐ecological resilience through water management archeologists can provide important information for modern communities facing similar problems. Archeology's long time perspective is very valuable. However, archeologists are confronted with a number of issues. Archeology can only study the material remains of past societies, not the living communities. Not all human activity translates into material residue and not all materials survive. Moreover, people will not demonstrate completely rational cause‐and‐effect behavior, but ideology and beliefs, which archeology can only poorly attest, will also have influenced decisions. Nevertheless, archeology can bring a unique perspective to the debate on climate change adaptation: archeology can falsify or corroborate sustainability claims, ancient water management techniques may still be a resilient mode of subsistence and ancient techniques often rely on relatively simple technology allowing for easier adoption. When transposing ancient water management techniques to modern situations it is important to involve stakeholders from an early stage, to incorporate traditional knowledge systems as much as possible and most importantly to ascertain whether physical and socio‐cultural circumstances are comparable. Archeological knowledge on ancient sustainability and water management is not a panacea for all climate related aridification, but can contribute a unique longue durée perspective. WIREs Water 2018, 5:e1256. doi: 10.1002/wat2.1256 This article is categorized under: Human Water > Water as Imagined and Represented Abstract : Location and schematic layout of the water management techniques mentioned in the text.